Looking beyond toxicities: Other health-related morbidities noted in childhood solid tumor survivors - Mehak Sehgal; Vishesh Jain; Sandeep Agarwala; Anjan Dhua; Prabudh Goel; Devendra Kumar Yadav; Sameer Bakhshi; Mani Kalaivani (Wolters Kluwer Medknow Publications, 2023)
Aim: In addition to the well-known toxicities of treatment, survivors of pediatric solid tumors can also develop other health-related conditions. They may either be an indirect consequence of therapy or could be unrelated to their prior history of malignancy. We aim to evaluate the nontoxicity related health conditions in survivors of pediatric solid tumors. Materials and Methods: The study included a cohort of hepatoblastoma (HB), Wilm's tumor (WT), and malignant germ cell tumors (MGCT) survivors registered at pediatric surgical-oncology clinic from 1994 to 2016. Follow-up was done according to standard protocols and children were evaluated at each visit for any health-related conditions. Results: Of the survivors, 318 survivors, comprising of 48, 81, and 189 survivors of HB, MGCT, and WT, respectively, were included in the analysis. We found 20.8% of patients with HB, 11.1% of patients with MGCT, and 16.4% of patients with WT to report nontoxicity-related health issues. A high prevalence of surgical conditions (3.4%), secondary malignancies (1.2%), gynecological conditions in girls (16.9%), tuberculosis (1.2%), gallstone disease (0.9%), pelvi-ureteral junction obstruction (0.9%), and neurological issues (0.9%) was noted. Two presumed survivors had died, one due to a late recurrence and the other due to a secondary malignancy. Conclusions: A high prevalence of medically or surgically manageable conditions makes it imperative to keep these children under follow-up to address any health-related conditions they may subsequently develop.